UFUS Impacta: new soybean cultivar for Minas Gerais State - Hamawaki, Osvaldo Toshiyuki; Juliatti, Fernando Cézar; Polizel, Analy Castilho; Amorim, Flávia Aparecida; Shigihara, Décio; Santos, Maria Amélia dos; Hamawaki, Cristiane Lemes (Pesquisa Agropecuaria Brasileira, 2005)
The search for soybean high yield without production costs increasing is the objective of genetic improvement. Cultivar UFUS Impacta is a soybean genotype originated from the cross between Cristalina RCH and IAC 100, semi-late maturity group, with an average productivity greater than the cheks Garantia and Emgopa 313 RCH. It is resistant to major soybean pathogens, and it is indicated for cultivation in the State of Minas Gerais, Brazil.